Criopreservação de agaricus blazei em nitrogênio líquido usando dmso como crioprotetor - Colauto, Nelson Barros (2012)
The preservation of Agaricus blazei is generally done using successive subcultivations that are laborious and are subject to contaminations or genetic degenerations, resulting in loss of biotechnological interest characteristics. An alternative process would be cryopreservation, but there are no reports of methodologies for this basidiomycete in liquid nitrogen. Thus, the objective of this study was to evaluate mycelial viability of A. blazei strains after cryopreservation in liquid nitrogen in order to establish the initial parameters of species preservation. Five strains grown on malt extract agar (MEA) were used. Disks of MEA containing A. blazei mycelium were transferred for screwcap cryovials containing the cryoprotectant, 10% dimethyl sulfoxide. Then, they were cooled at 8 °C for 30 min and kept at -196 °C with liquid nitrogen. After 1.5 year of cryopreservation, the cryovials were thawed in water bath at 30 °C for 15 min. The disks with mycelia were transferred to MEA culture media without cryoprotectant and kept at 28 °C for 30 days. A. blazei strains respond differently to the cryopreservation method at -196 °C by varying mycelial viability recovery. Cryopreservation with liquid nitrogen, using dimethyl sulfoxide as cryoprotectant, is not the most appropriate one for A. blazei preservation.